Do guns displace books? The impact of compulsory military service on educational attainment - Thomas K. Bauer; Stefan Bender; Alfredo R. Paloyo; Christoph M. Schmidt (Institute for the Study of Labor (IZA), 2011)
Compulsory military service typically drafts young men when they are at the height of their learning ability. Thus, it can be expected to depress the demand for higher education since skill atrophy and the delayed entry into the civilian labor market reduce the returns to human-capital investments. Attending university, however, might open the possibility to avoid the draft, leading to an increase in the demand for tertiary education. To estimate the causal effect of conscription on the probability to obtain a university degree, we use a regression-discontinuity design that employs special regulations associated with the introduction of conscription in Germany in 1956. We estimate conscription to increase the probability of having a university degree.
urn:nbn:de:101:1-201106201977
Keywords: I28; J24; 330; regression discontinuity; conscription; career interruption; skill atrophy; TS2SLS